Impacto de la falta de un estándar terminológico de prácticas en la interoperabilidad de Sistemas Informáticos en el sector salud - Mandirola Brieux, Humberto Fernán (2010)
We studied the impact of system implementation and maintenance cost which produce the absence of a terminological standard of master table of practices at national level to use in the interoperability of informatics systems in the health area in Argentina. Though during many years there existed an unique national master table of health practices used by all the providers and funders of medical services, unfortunately it has not been maintained for the last approximately 10 years and at present more than 50% of practices does not count with an agreed code and there exists a total anarchy in the technological field. In this way the creation of each data dictionary increase 50% the work of implementation of an interoperability between a provider and a funder in the implementation stage (10 hs average)and 20% (5 hours) in the hours of monthly maintenance. This multiplies exponentially when interoperability is implemented between several providers and funders. In our studied case, hours needed for implementation increase to 640.000 and hours needed for maintenance to 320.000. This could be avoided if there were an agreed terminological standard to use in interoperability.